Evaluating Technology Improvement in Sustainable Development Goals by Analysing Financial Development and Energy Consumption in Jordan - Fraihat, Baha Aldeen Mohammad; Ahmad , Ahmad Y. A. Bani; Alaa, Alrefai A.; Alhawamdeh, Abbas Mohammad; Soumadi, Mustafa Mohamed; Aln'emi, Ezaalden Ahmad Shutawe; Alkhawaldeh, Bashar Younis Subeih (International Journal of Energy Economics and Policy, 2023)
Sustainable development has become a crucial goal for policymakers worldwide, with technological progress playing a significant role in achieving this objective. Jordan, a developing country in the Middle East, has been working towards the attainment of Sustainable Development Goals (SDGs) by leveraging technology to promote economic growth while preserving the environment. In this study, we evaluate the impact of technological improvements on SDGs in Jordan by analyzing the relationship between financial development, energy consumption, and economic growth. The analysis covers the period from 1970 to 2021 and employs three econometric techniques, namely the Lee and Strazicich (2013) second-generation econometric approach, the novel Augmented Autoregressive Distributed Lag (AARDL) model, and Frequency Domain Causality (FDC) analysis. The results indicate a positive and significant association between financial development, energy use, and economic growth, with financial development having the strongest impact. Moreover, technological progress plays a crucial role in achieving SDGs by positively affecting financial development, energy consumption, and economic growth. This study highlights the importance of leveraging technology to promote sustainable development and provides valuable insights for policymakers in Jordan and other developing countries.